Peranan Lembaga Perlindungan Konsumen Swadaya Masyarakat Kota Medan dalam Memberikan Perlindungan Hukum Kepada Konsumen - Suwandi, Muhammad Ichsyan; Siregar, Taufik; Zulyadi, Rizkan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Regarding the Role of the Medan City Non-Governmental Consumer Protection Agency in Providing Legal Protection to Consumers, namely analyzing forms of legal protection, the role of the Medan City LPKSM in providing legal protection to consumers and the mechanism for establishing LPKSM as a Consumer Protection Agency in Medan City. This research was conducted at the UPT office. Medan Consumer Protection, LPKN DPP office, YPPKN DPP office, North Sumatra LPK-RI DPD office. This research uses a type of legal research and a normative-juridical research method. Because this type of research is a normative-juridical research method, the data obtained comes from library research and field research. Forms of legal protection for consumers through 2 channels, namely through channels outside the court and through the courts. Prior to filing a lawsuit in court, LPKSM must have a legal standing and/or mechanism at the time of formation, namely making a notarial deed of establishment of a legal entity engaged in consumer protection, obtaining a permit from the Ministry of Law and Human Rights, and making TDLPK at the local related agency. The role of LPKSM is to provide information to consumers, assist consumers in fighting for their rights, protect consumer rights, receive consumer complaints, conduct advocacy, provide assistance, supervise and collaborate with relevant agencies regarding consumer protection.